219 - THE INTERDISCIPLINARY IN THE PERTAINING TO SCHOOL PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
The present article deals with the interdisciplinary as being a process capable to transform Physical the Education Pertaining to school. To transform it in way that this disciplines can so be valued how much excessively you discipline that they integrate the pertaining to school resume, or either, this process is capable to stimulate the Pertaining to school Physical Education, therefore of to all them you inside discipline the same importance of the educational process. The interdisciplinary is a process that aims at the break of knowing them, without denying the specific idea . Its objective is to contextualize the contents of disciplines them, making with that  they search one same objective, in way that this process is not a way of only hand, but that it can be established by diverse you discipline and of diverse forms. The process to interdisciplinary cousin for a transforming education, that contributes for the formation of critical citizens, that fight inside for its ideals of the society where they live. Another proportionate fact for the interdisciplinary is the contribution  so that the beginning of the Inclusion it can be placed in practical. At last, the interdisciplinary makes possible to the professor of Physical Education the construction of activities that run away from the exacerbated valuation of the performance and the efficiency, making possible that all the pupils participate actively of the lessons, each one with its proper contribution.
Keywords: interdisciplinary; Physical Education; social transformation